Maintenance therapy with oral decitabine plus cedazuridine after allogeneic stem cell transplantation for myelodysplastic syndrome - Portia Smallbone; Terri Lynn Shigle; Oren Paslovsky; Chitra Hosing; Amin Alousi; Qaiser Bashir; Yosra Aljawai; Jeremy Ramdial; Uday Popat; Richard Champlin; Elizabeth J. Shpall; Betül Oran (Haematologica, 2025)
Disease relapse remains the primary challenge for patients undergoing allogeneic transplantation (HSCT) for myelodysplastic syndrome (MDS). Maintenance therapies with hypomethylating agents are under investigation for use in mitigating relapse in high-risk patients. In this retrospective study, we assessed the safety and efficacy of oral decitabinecedazuridine maintenance in 18 high-risk MDS patients post-HSCT. 66.7% (n=12) received decitabine-cedazuridine (35/100mg) on days 1 and 3, while 33.3% (n=6) received therapy on days 1-3. Patients completed a median of six treatment cycles (range; 1-20), with one third of patients completing all planned cycles. No unexpected adverse events were observed, with the primary toxicity being myelosuppression. Grade 1-2 upper respiratory tract infections occurred in 4 patients, and fungal pneumonia in one patient. Overall, patients achieved a median 2-year relapse-free survival (RFS) of 66.7% (95% CI, 40.4-83.4%) and 2-year overall survival of 72.2% (95% CI, 45.6%-87.4%), with relapses occurring predominantly in TP53- mutated cases. Prospective clinical trials are essential to confirm the best tolerated dose with potential to improve transplant outcomes.